2003
DOI: 10.1149/1.1554915
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of Titanium and the Electrodeposition of Al-Ti Alloys in the Lewis Acidic Aluminum Chloride–1-Ethyl-3-methylimidazolium Chloride Melt

Abstract: The chemical and electrochemical behavior of titanium was examined in the Lewis acidic aluminum chloride-1-ethyl-3methylimidazolium chloride (AlCl 3 -EtMeImCl) molten salt at 353.2 K. Dissolved Ti͑II͒, as TiCl 2 , was stable in the 66.7-33.3% mole fraction ͑m/o͒ composition of this melt, but slowly disproportionated in the 60.0-40.0 m/o melt. At low current densities, the anodic oxidation of Ti͑0͒ did not lead to dissolved Ti͑II͒, but to an insoluble passivating film of TiCl 3 . At high current densities or ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
129
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(142 citation statements)
references
References 36 publications
13
129
0
Order By: Relevance
“…A representative ionic liquid used for the electrodeposition of Al alloys is Lewis acidic 1-ethyl-3-methylimidazolium chloride (EMIC)-AlCl 3 (where the AlCl 3 /EMIC molar ratio >1). Reports on the electrodeposition of Al alloys including Al-Ni, 13 Al-Ti, 14 Al-V, 15 Al-Zr, 16 Al-Mo, 17 Al-Mn, 18 and Al-Hf 19 are available in the literature. A previous study revealed that electrodeposition in a EMIC-AlCl 3 bath with the addition of W(IV) chloride (WCl 4 ) yielded Al-W alloys, but the W content was lower than 1 at.%.…”
mentioning
confidence: 99%
“…A representative ionic liquid used for the electrodeposition of Al alloys is Lewis acidic 1-ethyl-3-methylimidazolium chloride (EMIC)-AlCl 3 (where the AlCl 3 /EMIC molar ratio >1). Reports on the electrodeposition of Al alloys including Al-Ni, 13 Al-Ti, 14 Al-V, 15 Al-Zr, 16 Al-Mo, 17 Al-Mn, 18 and Al-Hf 19 are available in the literature. A previous study revealed that electrodeposition in a EMIC-AlCl 3 bath with the addition of W(IV) chloride (WCl 4 ) yielded Al-W alloys, but the W content was lower than 1 at.%.…”
mentioning
confidence: 99%
“…Figure 4 shows SEM images of Al-W-Mn alloy samples prepared at three different applied current densities under two different bath conditions. In each bath, as is the case for Al-Ti alloy electrodeposition from the 66.7 m/o IL, 6 the nodule size of the alloy samples becomes larger with an increase in the magnitude of −j t . At higher MnCl 2 bath concentrations, spherical shaped deposits were obtained regardless of the applied current densities as shown in Figs.…”
Section: Resultsmentioning
confidence: 91%
“…Among the chloroaluminates, AlCl 3 -1-ethyl-3-methylimidazolium chloride (AlCl 3 -[C 2 mim]Cl) IL is under development for industrial-scale aluminum plating and for lab-scale aluminum alloy electrodeposition. 5 A great number of aluminum-transition metal alloys including AlCu, 5 Al-Ag, 5 Al-Ni, 5 Al-Ti, [5][6][7] Al-V, 8 Al-Cr, 5 Al-Mn, 5 Al-Mo, 9 AlZr, 10 Al-Hf, 11 Al-W, 12 Al-In-Sb, 13 Al-Mo-Ti, 14 and Al-Mo-Mn 15 have been electrodeposited from the Lewis acidic composition [percent mole fraction of the AlCl 3 > 50] of the AlCl 3 -[C 2 mim]Cl IL. The processes leading to these alloys can be divided into underpotential and overpotential deposition.…”
mentioning
confidence: 99%
“…Cyclic voltammetry was conducted by a common cell previously reported in our paper. 31,42,43 A platinum wire electrode (Nilaco, φ 1 mm, 99.8%) was used as the working electrode, and coils of 1 mm diameter aluminum wire (Nilaco, 99.999%) were used as the counter and reference electrodes. The aluminum electrodes were cleaned with a mixture of concentrated H 2 SO 4 , HNO 3 , and H 3 PO 4 , rinsed with distilled H 2 O, and dried under vacuum before use.…”
Section: -35mentioning
confidence: 99%